1976
DOI: 10.1111/j.1469-8986.1976.tb03344.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Velocity as a Measure of Blood Pressure Change

Abstract: The use of arterial pulse wave velocity (PWV) as a continuous measure of blood pressure changes is outlined. Theoretical considerations indicate that changes in PWV reflect changes in blood pressure, and an experiment was carried out to assess this relationship. PWV along an arm artery was monitored in 26 subjects at a time when the arterial distending pressure of the limb was altered over a wide range by means of externally applied positive and negative pressures. The results show that changes in PWV reliably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
0
2

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(98 citation statements)
references
References 23 publications
(20 reference statements)
5
91
0
2
Order By: Relevance
“…These changes were also clearly seen in the PTT/SBP slopes, which were used to estimate changes in SBP from changes in PTT. 29,30 Our data also indicated that about half of the changes with blood pressure were direct and were not mediated via an age effect. HR was only weakly associated with PTT, and for the ear site only.…”
Section: Discussionsupporting
confidence: 60%
“…These changes were also clearly seen in the PTT/SBP slopes, which were used to estimate changes in SBP from changes in PTT. 29,30 Our data also indicated that about half of the changes with blood pressure were direct and were not mediated via an age effect. HR was only weakly associated with PTT, and for the ear site only.…”
Section: Discussionsupporting
confidence: 60%
“…The Pulse transit time (PTT) and pulse arrival time (PAT) are promising non-invasive techniques for continuous blood pressure monitoring, particularly for detecting short-term perssure changes [7,8]. The PTT, defined as the the time delay for the pressure wave to travel between two arterial sites, and the PAT, defined as the interval between the R-wave in the ECG and a distal arterial pulse, are both negatively associated with blood pressure [9].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this is in contrast to results from experiments using alternative techniques, which suggest that the increase in arterial stiffness in hypertensive individuals is largely because of the increase in mean pressure. 8,9 The 2 questions one must surely ask are, first, why do these findings seem to disagree with the findings of others using different methodology, and second, what relevance might these observations have from a clinical perspective?…”
mentioning
confidence: 95%
“…Previous work has either used pressure-compliance curves with interpolation of stiffness at a given blood pressure (BP) 8 or has normalized transmural pressure by placing the arm in a pressurized air chamber. 9 However, in this issue of Hypertension, Stewart et al 10 describe a method for generating isobaric conditions using a pharmacological intervention that acutely normalized the loading pressure in hypertensive subjects, dispensing with some of the assumptions associated with other methods. Stewart et al 10 studied 20 subjects with treated but inadequately controlled essential hypertension and 20 matched normotensive controls.…”
mentioning
confidence: 99%